Agential Epistemic Injustice in Clinical Interactions Is Bad for Medicine - Lisa Bortolotti (Philosophy of Medicine)
In interactions characterized by agential epistemic injustice, the interpreter avoids engaging with the speaker’s perspective and challenges or distorts the speaker’s contribution before taking time to explore it. Where the success of the interaction depends on a genuine knowledge exchange between interpreters and speakers, epistemic injustice compromises the success of the interaction. Building on recent qualitative work on communication in youth mental health, I argue that clinical interactions are less likely to achieve their aims when practitioners fail to engage with the perspective of the person seeking support, and challenge or distort the person’s contribution before taking time to explore it.